2012
DOI: 10.1002/hyp.9506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of catchment and network delineation approaches in complex suburban environments: application to the Chaudanne catchment, France

Abstract: Suburban areas are subject to strong anthropogenic modifications, which can influence hydrological processes. Sewer systems, ditches, sewer overflow devices and retention basins are introduced and large surface areas are sealed off. The knowledge of accurate flow paths and watershed boundaries in these suburban areas is important for storm water management, hydrological modelling and hydrological data analysis. This study proposes a new method for the determination of the drainage network based on time efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…The flow of stormwater in urban areas does not necessarily follow the topography due to obstacles such as buildings or street curbs [32]. Jankowfsky et al [33] showed for a peri-urban catchment in France that catchment properties (such as the drainage area) differed significantly when either only a DEM was used for delineation or the topographical information was complemented with field survey data. They stated, however, that for large parts of the catchment only a DEM with a low spatial resolution (25 m) was available.…”
Section: Introductionmentioning
confidence: 99%
“…The flow of stormwater in urban areas does not necessarily follow the topography due to obstacles such as buildings or street curbs [32]. Jankowfsky et al [33] showed for a peri-urban catchment in France that catchment properties (such as the drainage area) differed significantly when either only a DEM was used for delineation or the topographical information was complemented with field survey data. They stated, however, that for large parts of the catchment only a DEM with a low spatial resolution (25 m) was available.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the associated sewer infrastructure might transfer water between different natural (sub)catchments and further affect the natural hydrological processes in the catchment (Simmons and Reynolds, 1982). Recent research on catchment delineation considered incorporation of these changes in hydrological flow paths using semi-automated procedures (Jankowfsky et al, 2013). Such delineations, however, remain largely data dependent and time consuming.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…After calibration of the large set of parameters in such models, a better match between simulated and observed hydrological variables may be obtained, but this does not necessarily mean that the model has a good accuracy. Model over parameterization and related parameter identifiability problems are well-known pitfalls (Beven, 1989;Jakeman and Letcher, 2003;Muleta and Nicklow, 2005). These problems limit the applicability of such models.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The periurban space is composed of small objects, with small areas such as individual 23 houses, narrow roads, hedges... Their identification requires the use of VHR (Very High 24 Resolution) images. This spatial constraint led us to choose images taken from optical 1 sensors which presently offer the highest resolutions.…”
Section: Building Of the Data Set 16 17mentioning
confidence: 99%
“…The use of these attributes allowed solving 20 the spectral confusions between for example, porous mineral areas (plowed) and 21 impervious mineral areas (artificial areas), the urban objects being generally of smaller 22 size as compared to farming land. 23 The recording date of the image played an important role. It impacted the development 24 stage of the vegetation and especially the cover fraction of herbaceous vegetation, 25 24 which grows from bare soil to low and then high chlorophyll content vegetation.…”
Section: Large Catchment 9 10mentioning
confidence: 99%